Apakah Keputusan Pembelian Konsumen Java Origin Terkait Dengan Pemasaran Produk Online? - Liliana Dewi; Liem Evan Wiryono (BIP's JURNAL BISNIS PERSPEKTIF, 2020)
Java Origin is a company that produces batik shirts in modern design by using mixing cloth and denim fabric. This study aims to determine the influence of online media and personal selling of people in this research to know the purchasing decisions of Java Origin consumers. Determination of source data used samples saturated with 77 respondents, that is consumers who have purchased Java Origin products. The method in this research is a quantitative method. This data retrieval method uses a questionnaire that is distributed directly by using multiple linear regression as a data analysis technique. The result of this research is the online media and personal sale variable influence significant to a decision of purchasing Java Origin.